Halal industry in ASEAN: issues and challenges - Abdullah, Moha Asri; Azam, Md Siddique (IGI Global, 2020)
Amongst three Muslim majority countries (Indonesia, Malaysia, and Brunei) of ASEAN, Malaysia leads the halal industry globally and considered to be the global halal hub. Simultaneously, the market is growing tremendously in other member countries as well. It has been realized that a number of driving forces are responsible for boosting the expansion of Halal industry globally as well as in ASEAN. While there are a number of factors accelerating the growth of the Halal industry, there are many limitations and challenges that are hindering the market expansion. Therefore, this chapter introduces the overview of Halal industry globally as well as in ASEAN counties. The chapter explores the opportunities of the Halal industry for ASEAN counties followed by identifying the issues and challenges confronted by industry players. Finally, it concludes by providing some recommendations in the ASEAN context based on the current global situation and findings of the Halal industry. The chapter adopts methodology of analyzing secondary data.